Pile-up correction for coincidence counting using a CAEN 1724 digitizer - Guilherme Soares Zahn; Iberê Souza Ribeiro Jr; Frederico Antonio Genezini (Brazilian Journal of Radiation Sciences, 2019)
In conventional gamma-ray spectrometry, the probability of pile-up effects is considered to be proportional to the dead-time, and is usually neglected for low dead-times (below 4-5%). In gamma-gamma coincidence spectrometry, though, while the dead time takes into account only events that are actually digitized, the pile-up effects are proportional to the actual gamma-ray detection rate in each detector, not only to the ones that trigger the coincidence gate. Thus, the pile-up corrections may not be so easy to assess as in single spectrometry systems. In this work, a system composed of two HPGe detectors coupled to a CAEN v1724 digitizer is studied. A 3kBq 60Co source was analyzed, both alone and in the presence of other radioactive sources (137Cs, 133Ba and 152Eu), and the resulting coincidence peak areas were compared to assess the effectiveness of two distinct corrections: a simple normalization by the live time of acquisition and the normalization by the count rate obtained using a pulse generator. The results obtained stress the need to use the pulse generator in this specific setup in order to get accurate results.